Moral Formation and Character Education of Children Through Discussion Method in Donorejo Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Early childhood character education is crucial for forming both people and society. However, implementing successful character education programs continues to present difficulties. Through Participatory Action Research (PAR), this study seeks to understand these issues better and identify solutions. Teachers, parents, and kids are the major participants in this research process. Role-playing and classroom discussions were part of the research methodology used to understand how youngsters conceptualize moral and ethical principles. The study's findings indicate that interactive discussions and role plays can help kids learn moral and ethical principles and motivate them to live by them. This study demonstrates the value of a participatory approach.